E-003 Aneurysm Re-treatments Following Recurrences After Initial Use of the Pipeline Embolization Device. (26th July 2014) - Park, M; Nanaszko, M; Sanborn, M; Moon, K; McDougall, C; Albuquerque, F
Abstract : Introduction: Although the Pipeline Embolization Device (PED, eV3 Neurovascular, Irvine, California) has provided the field of neuro-interventional surgery with a significant leap forward in the treatment of cerebral aneurysms, treatment failures still exist with this new platform. We sought to examine our experience with re-treatments of cerebral aneurysms after initial treatment with the PED. Materials and methods: We retrospectively examined our prospectively maintained endovascular neurosurgical database for cerebral aneurysm treatment failures using the PED from May 2011 to the present time. Nine patients (1 male, 8 female; Age range 28–83 yrs, average age 54.4 yrs, SD 17.5 yrs) treated for nine aneurysms (Average size 17.7 mm, SD 11.9 mm) out of 137 total patients treated with PED were identified during our study period (6.6% re-treatment rate, 9/137). Results: Of the nine re-treatments, six were due to persistent filling of the aneurysm, while three were re-treated due to PED contraction/migration at an average time interval of 6.9 months (SD 3.7 months). Following the initial treatment and at the time of re-treatment, all aneurysms had a Raymond 3 occlusion. Despite this, the angiographic appearance of the aneurysms at the time of re-treatment remained the same in 2, better in 6, and worse in 1. At the last follow-up, two aneurysms had a Raymond 1 occlusion, three aneurysms had a Raymond 2 occlusion, and four aneurysms had a Raymond 3 occlusion. Eight aneurysms had better angiographic outcomes versus one aneurysm with a worse angiographic outcome since the re-treatment. Conclusion: While there is a low rate of treatment failure following use of the PED, re-treatments can be performed in a safe and effective manner and lead to continued angiographic improvements on long term follow-up. Disclosures: M. Park: None. M. Nanaszko: None. M. Sanborn: None. K. Moon: None. C. McDougall: None. F. Albuquerque: None.